Processing of α-Fe2O3 Nanoparticles on Activated Carbon Cloth as Binder-Free Electrode Material for Supercapacitor Energy Storage. (January 2021) - Orisekeh, K.; Singh, B.; Olanrewaju, Y.; Kigozi, M.; Ihekweme, G.; Umar, S.; Anye, V.; Bello, A.; Parida, S.; Soboyejo, W.O.
Highlights: Activation (functionalization) of the CC introduced functional groups to the CC. The effects of α-Fe2 O3 deposited on carbon cloth (CC) and Activated carbon cloth (ACC) was investigated. Uniform and dispersed α-Fe2 O3 nanoparticles was achieved on the ACC due to the activation of the surface. The activation resulted in electrodes with Specific Capacity of 295.56 mAhg −1 with excellent cyclic stability. Abstract: The need for flexible energy storage devices has stimulated the interest in the development of nanostructures in supercapacitors for energy storage. In this work, a hydrothermal method is used to optimize the growth of α-Fe2 O3 nanoparticles on carbon cloth (CC) and activated carbon cloth (ACC). The resulting composition, morphologies and microstructures displayed interesting features that are suitable as electrodes material for electrochemical capacitors. These are integrated as binder-free, symmetric device, which were then assembled and tested. The device assembled with the activated carbon cloth exhibited higher electrochemical performance (specific capacity of 295.56 mAhg −1, specific energy of 37 WhKg −1 and specific power of 0.5 kWKg −1 in a 3 M KOH electrolyte at 1 A g −1 . The device also had good capacitance retention of 96.6 % after 10000 charge-discharge cycles. The implications of the results are discussed for potential applications of the α-Fe2 O3 -ACC in supercapacitors for energy storage systems that address global energy needs.